Perinatal exposure to insecticide fipronil: Effects on the reproductive system in male rats - De Barros, Aline L. [UNESP]; Bae, Julie H. [UNESP]; Borges, Cibele S. [UNESP]; Rosa, Josiane L. [UNESP]; Cavariani, Marilia M. [UNESP]; Silva, Patrícia V. [UNESP]; Pinheiro, Patricia F. F. [UNESP]; Anselmo-Franci, Janete A.; Arena, Arielle C. [UNESP] (CSIRO Publishing, 2017)
Fipronil is an insecticide widely used in agriculture, veterinary medicine and public health that has recently been listed as a potential endocrine disrupter. In the present study we evaluated the effects of perinatal exposure to fipronil during the period of sexual brain differentiation and its later repercussions on reproductive parameters in male rats. Pregnant rats were exposed (via gavage) to fipronil (0.03, 0.3 or 3mgkg-1) from Gestational Day 15 until Postnatal Day 7. Fipronil exposure did not compromise the onset of puberty. In adulthood, there was no effect on organ weight or sperm production. Furthermore, there were no adverse effects on the number of Sertoli cells per seminiferous tubule, testicular and epididymal histomorphometry or histopathology or expression patterns of androgen receptor in the testis. Similarly, no changes were observed in the sexual behaviour or hormone levels. However, in rats exposed to fipronil, changes in sperm motility were observed, with a decrease in motile spermatozoa and an increase in non-mobile spermatozoa, which can compromise sperm quality in these rats. Perinatal exposure to fipronil has long-term effects on sperm parameters, and the epididymis can be a target organ. Additional studies should be undertaken to identify the mechanisms by which fipronil affects sperm motility.
Keywords: Endocrine disruptors; Sperm motility